THE INFLUENCE OF HUMAN CAPITAL AND SOCIAL CAPITAL ON THE PERFORMANCE OF MSMES IN MEDAN CITY (FINANCIAL ACCESS AS A MODERATION VARIABLE) - Daniel Dohar Parulian; Syech Suhaimi; Irsad Lubis (RADJA PUBLIKA, 2025)
This study aims to analyze and determine the influence of Human Capital and Social Capital on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Medan City, with Financial Access serving as a moderating variable. The independent variables in this study are Human Capital and Social Capital, while the dependent variable is MSME performance. The research uses primary data collected from 100 respondents. Data collection methods include interviews, observations, and questionnaires, and the data were analyzed using Structural Equation Modeling (SEM) approach with the Smart PLS 4 software. The result show that Human Capital has a positive but not significant effect on the performance of MSMEs in Medan City. Social Capital has a positive and significant effect on MSME performance. Financial Access has a positive and significant effect on MSME performance in Medan. However, Financial Access does not function as a moderating variable in the relationship between Human Capital and MSME performance, nor in the relationship between Social Capital and MSME performance.